Dinamika Alih Kode dan Negosiasi Identitas dalam Komunikasi Pola Asuh Keluarga Migran Indonesia - Asfa Davi Bya; Moch. mukhlison (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study examines code-switching dynamics in parenting communication among two Indonesian migrant families who have acquired Malaysian citizenship. Using a qualitative approach with an intrinsic case study design, data were collected through in-depth interviews and observation of four informants comprising parents (First Generation) and children (Second Generation). Analysis was conducted using Poplack's (1980) typology, Gumperz's (1982) sociopragmatic framework, and Spolsky's (2004) language ideology perspective. Findings indicate that intra-sentential switching is the most productive form with Malay functioning as the matrix language, addressee specification emerges as the most dominant function, and message qualification reveals a negative pattern in which Indonesian is no longer effective as a command reinforcer. Second Generation informants in both families tend to identify as Malaysian, with varying intensity that correlates directly with the degree of Indonesian language exposure at home. Code-switching among First Generation informants is shown to function as a deliberate identity strategy, whereby Indonesian is selectively maintained in specific domains as a conscious effort to preserve cultural ties amid the dominance of Malay in everyday life.